Clinical-pharmacist intervention reduces clinically relevant drug–drug interactions in patients with heart failure: A randomized, double-blind, controlled trial. (15th January 2016) - Roblek, Tina; Deticek, Andreja; Leskovar, Bostjan; Suskovic, Stanislav; Horvat, Matej; Belic, Ales; Mrhar, Ales; Lainscak, Mitja
Abstract: Background: Incidence of drug–drug interactions (DDIs) increases with complexity of treatment and comorbidities, as in heart failure (HF). This randomized, double-blind study evaluated the intervention of the pharmacist on prevalence of clinically relevant DDIs (NCT01855165 ). Methods: Patients admitted with HF were screened for clinically relevant DDIs, and randomized to control or intervention. All attending physicians received standard advice about pharmacological therapy; those in the intervention group also received alerts about clinically relevant DDIs. Primary endpoint was DDI at discharge and secondary were re-hospitalization or death during follow-up. Results: Of 213 patients, 51 (mean age, 79 ± 6 years; male, 47%) showed 66 clinically relevant DDIs and were randomized. For intervention (n = 26) versus control (n = 25), the number of patients with and the number of DDIs were significantly lower at discharge: 8 vs. 18 and 10 vs. 31; p = 0.003 and 0.0049, respectively. Over a 6 month follow-up period, 11 control and 9 intervention patients were re-hospitalized or died (p > 0.2 for all). No significant differences were seen between control and intervention for patients with eGFR < 60 mL/min/1.73 m 2 (78%) for re-hospitalization or death (10 vs. 7; p = 0.74). Conclusions: Pharmacist intervention significantly reduces the number of patients with clinically relevant DDIs, but not clinical endpoints 6 months from discharge.